The Rise of Self-Interests: How Shifting Political Goals Changed the Effectiveness of Dutch Official Development Aid to Bangladesh From 2005 Until 2016 - Oomen, Thomas L. (UI Scholars Hub, 2020)
Aid effectiveness has been situated in the central debate of development studies and, particularly, among foreign aid policy making community. As the Netherlands was one of the unique countries which focused extensively on the needs of its recipient, it is important to investigate the Netherlands’ recent practice of its development aid, particularly to Bangladesh and the associated goal ambiguity. This article attempts to answer the question, “to what extent does goal ambiguity in Dutch development aid affect the effectiveness of Dutch development aid given to Bangladesh?” This analysis is based on independent assessments of Dutch official development aid (ODA) to Bangladesh and Dutch coalition agreements in 2005-2010 and 2011-2016. This study finds that, in the second period, goal ambiguity has increased, while the aid effectiveness has decreased. This change is unlikely to be attributed to the conditions for aid effectiveness since these remained largely stable or even in slightly in favour of the second period. While the comparison of different sectors between timeframes lacks full robustness, there is direct evidence that goal ambiguity has played a role in lower effectiveness in the water related aid in the second period. Therefore, this study suggests that aid effectiveness in Bangladesh has decreased in the period 2011 to 2016 due to an increase in goal ambiguity caused by increasing self-interests in Dutch ODA policy.